Methods For Generating Cryptographic Keys From Online Hand Signatures - Yip, Wai Kuan (2007)
In this thesis, we are interested in using online signatures as the biometric input. The motivation behind our work is to find a convenient (in terms of coast and availability) and widely used biometric factor for use with cryptographic framework. There are several ways to incorporate these two technologies, including using a private key to encrypt the biometric and vice versa.